Biological dynamics of a polish rulal community in the XIX century. I. General demographical characteristics - Henneberg, Maciej (Anthropological Review, 1977)
The paper presents a part of results obtained during examination of data on briths, deaths and marriages recorded in the registers of Szczepanowo parish in the years 1820-1874. To the parish belong 14 villages situated in N-E part of Great Poland (Wielkopolska) — see fig. 1. Examination of the data was undertaken within Biological History of Human Populations Research Program in order to obtain information on changes in gene pools occuring in the period of socio-economic change (for details see Borowski 1969) in this part of Poland. This research is coordinated with observations of earlier skeletal samples and modern population from the same region. The region (or as some authors prefer — microregion) of Szczepanowo is considered as being settled by a local group „typical” for rural eco-cultural conditions of Wielkopolska. In the future works we intend to present details on operation of natural selection in the population and its mating system. However, the first objective is to prove that the data at hand are representative for an „average village” of the large territory. To this end in the present paper are given several basic demographic characteristics of the parish as well as their comparison with available demographic information pertaining to the large part of Poland.On the figure 3 are presented numbers of births and deaths in an „average settlement” of the parish, Great fluctuations of mortality in the first half of 19th century (due mainly to epidemies and famine) are consistent with observations for the entire Polish territory under German rule (see Borowski 1967, 1969). Selected parameters of life tables calculated with assumed stationary population state are given in the table 2. Table 3 presents parameters of life tables calculated for longer periods with assumed stationary (left columns) and stable (right columns) population states. Respective rates of natural increase for assumed stable state are calculated on the basis of crude births and deaths rates presented together with crude marriage rate on the figure 5. Number of inhabitants an "average settlement” was estimated on the basis of births, deaths and marriages numbers with the use of two methods explained in the text. Final estimate may be seen in the column C of the table 7. With known number of inhabitants and area it was possible to estimate population density (the first column of the table 8). Finally there was an opportunity to infer on social structure of the group from entries in birth records concerning parent's “status”. Respective data are shown in the table 9. It follows that only about 1/3 of families owned farms (many of them too small for supporting a family), the rest of inhabitants made their living mainly as hired farmhands, occasionaly also as craftsmen, fishers, foresters cie. (see line “inni” in the table 9.).On grounds of comparisons with information given by other authors and general demographic knowledge it can be concluded that inhabitants of Szczepanowo parish constituted a sample representative for 19th century Great Poland rural populace.